The art of Pere Joan : space, landscape, and comics form - Fraser, Benjamin (World comics and graphic nonfiction series., 2019)
A close reading of the innovative, distinctive vision of Pere Joan, who has pushed boundaries in Spain's comics scene for more than four decades and stoked a new understanding of the nature of reading comics.